Technology Trust and Intent to Use: The Mediating Effect of Quick Restaurant Self-Service Kiosks Aesthetics - Angila G. Abarro; Anna Asrina I. Abdullah; Nadyne A. Gabia; Irish Janelle A. Gimenez; John Vincent G. Nacario; Jayvie O. Guballo (Journal of Management Studies and Development, 2026)
This study examines how customers develop trust and intention to use self-service kiosks within quick-service restaurants. As digital systems become more common in food service, it is crucial to understand how users respond to both the functionality and aesthetics of kiosks. This research focuses on the mediating effect of self-service kiosk aesthetics on the relationship between technology trust and intent to use. Participants were individuals who used self-service kiosks and resided in Mandaluyong City, selected through a two-stage cluster sampling technique. Using a quantitative correlational design and Partial Least Squares-Structural Equation Modeling (PLS-SEM), the analysis confirmed that all constructs were valid and reliable. The results showed significant positive relationships between technology trust, self-service kiosk aesthetics, and intent to use. Mediation analysis further revealed that self-service kiosk aesthetics partially mediates this relationship, indicating that while technology trust directly increases intent to use, its influence becomes stronger when customers perceive the kiosk as visually appealing, simple, harmonious in color, and interactively designed. These findings suggest that self-service kiosk aesthetics is not merely an external feature but an indispensable component, and that investing in kiosk aesthetics functions as an investment in technology trust itself, which contributes to higher intent to use. Overall, the study enhances understanding of SSTs adoption by showing that aesthetic qualities work together with system functionality to encourage customer acceptance in quick-service restaurant settings.